What Courses Do I Need to Teach in Order to Address Food Insecurity in Sub Saharan Africa? A Delphi Study - Carla Andrea Millares Forno; Amy E. Boren-Alpizar; Todd Brashears (Journal of International Agricultural and Extension Education, 2019)
Sub Saharan Africa is a region that has been struggling with food insecurity for decades. Though the percentage of undernourished people in the region has decreased over the last 25 years, the actual number of undernourished people increased by more than forty million. Combatting food insecurity in the region requires an arsenal of skills, knowledge, and abilities across a broad range of disciplines. One way to target food insecurity is through education and capacity building. The purpose of this study was to identify the courses and topics that should be included in a food security (FS) graduate certificate focused on Sub Saharan Africa. Identification of the topics and courses came from faculty and professionals working in the FS field in Sub Saharan Africa. A three-round Delphi technique was conducted to accomplish the purpose of the study with a total of 63 experts. Of the original 101 topics that the expert panel proposed in Round One, 80 reached the level of agreement. Researchers grouped the topics into 28 courses. The final result of the study was 24 courses that reached the level of agreement for determining the main topics and courses that should be included in a graduate certificate focused on FS for Sub Saharan Africa.
Keywords: food security; Delphi; agricultural education; Sub Saharan Africa